2013
DOI: 10.1111/nph.12274
|View full text |Cite
|
Sign up to set email alerts
|

The metabolite chemotype of Nicotiana benthamiana transiently expressing artemisinin biosynthetic pathway genes is a function of CYP71AV1 type and relative gene dosage

Abstract: SummaryArtemisia annua, which produces the anti-malaria compound artemisinin, occurs as highartemisinin production (HAP) and low-artemisinin production (LAP) chemotypes. Understanding the basis of the difference between these chemotypes would assist breeding and optimising artemisinin biosynthesis.Here we present a systematic comparison of artemisinin biosynthesis genes that may be involved in determining the chemotype (CYP71AV1, DBR2 and ALDH1). These genes were isolated from the two chemotypes and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 29 publications
(73 reference statements)
0
71
0
Order By: Relevance
“…In addition, the tissue-specific expression profiles thus obtained may be further correlated with the expected product accumulation profiles of the tissue in question. In this manner, we have recently identified and characterized the genes of the costunolide [17] and artemisinin biosynthetic pathways [18,19].…”
Section: Strategies For Isoprenoid Gene Identification and Characterimentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the tissue-specific expression profiles thus obtained may be further correlated with the expected product accumulation profiles of the tissue in question. In this manner, we have recently identified and characterized the genes of the costunolide [17] and artemisinin biosynthetic pathways [18,19].…”
Section: Strategies For Isoprenoid Gene Identification and Characterimentioning
confidence: 98%
“…The pathway genes were also stably transformed into tobacco, resulting in trace artemisinin detection [34]. Furthermore, transient expression of all known artemisinin biosynthetic genes in N. benthamiana showed that changes in the relative activity of the individual steps can improve the flux to the dihydro artemisinic acid (DHAA) segment of the pathway, ultimately leading to improved artemisinin production [18]. As the conversion mechanism of dihydroartemisinic acid to artemisinin in planta remains elusive, the full potential for production of the valuable antimalarial in heterologous plant systems has not yet been satisfactorily explored.…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“…CYP71AV1 in the low artemisinin-chemotype has extra amino acid residues in its N-terminal, whereas CYP71AV1 in the high-artemisinin chemotype has not such extension. Upon transient expression in N. benthamiana, high artemisinin-chemotype CYP71AV1 exhibits higher enzyme activity than low artemisinin-chemotype CYP71AV1 (Ting et al 2013).…”
Section: Why Are There Different Chemotypes With Low-and High-level Amentioning
confidence: 99%
“…Nevertheless, the multiple enzymatic routes to artemisinic acid and dihydroartemisinic acid have been validated, as illustrated in Figure 1 (Ting et al 2013). Overall, intermediates were identified and assigned sequentially, enzymes were purified and structurally/functionally characterized, and encoding genes were cloned and homologously/ heterologously expressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation